Advertisement in the EAEU Countries: Law Harmonization Issues - DORSKI, Andrei Y.; PAVLENKO, Evgeniya M.; SHUTIKOVA, Nataliya S.; ZUBANOVA, Svetlana G.; PASHENTSEV, Dmitriy А. (Journal of Advanced Research in Law and Economics; Vol 8 No 7 (2017): JARLE Volume VIII Issue 7(29) Winter 2017, 2017)
The rapprochement of economic laws, set forth in the Treaty on the Eurasian Economic Union (EAEU), provides for the unitary standards of disseminating economic information. In the mid-1990s, Russia became a model in regulating advertising activities for the majority of the FSU (Former Soviet Union) republics. Nevertheless, the article presents substantial differences in advertisement understanding in the EAEU that can slow down the turnover expansion. It is demonstrated that even the same words can have different meaning. The paper analyzes the drawbacks in different approaches. In particular, it concludes that lawmakers do not pay enough attention to the regulation of advertisement in the new communication media. The author outlines some opportunities to eliminate the drawbacks in the process of bringing together the laws.